(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Digital transformation has presented a number of new challenges to national resilience, one of which is the increase in cyber threats, such as the spread of hoaxes and hate speech that can disrupt national unity. In this context, it is very important to strengthen the spirit of state defense, especially among students who act as agents of change. This study aims to explore the role of students, especially the Student Regiment Activity Unit (UKM Menwa) of the University of Jember, in implementing state defense values and improving digital literacy. The method used in this research is library research with a qualitative descriptive approach, which is based on the analysis of various literatures and official documents. The results of the study show that UNEJ Menwa UKM makes a significant contribution in building students’ national character through training activities, securing campus events, and community service. In addition, Menwa also actively conducts socialization and hoax detection training as an effort to increase digital literacy awareness among students. However, this study also noted several obstacles, such as low student participation, limited digital literacy, and lack of resources. Therefore, stronger institutional support and collaborative strategies are needed so that digital literacy-based state defense programs can be implemented optimally and effectively. Transformasi digital telah menghadirkan sejumlah tantangan baru bagi ketahanan nasional, salah satunya adalah meningkatnya ancaman siber, seperti penyebaran hoaks dan ujaran kebencian yang dapat mengganggu persatuan bangsa. Dalam konteks ini, sangat penting untuk memperkuat semangat bela negara, terutama di kalangan mahasiswa yang berperan sebagai agen perubahan. Artikel ini bertujuan untuk mengeksplorasi peran mahasiswa, khususnya Unit Kegiatan Mahasiswa Resimen Mahasiswa (UKM Menwa) Universitas Jember, dalam menerapkan nilai-nilai bela negara serta meningkatkan literasi digital.Metode yang digunakan dalam Artikel ini adalah studi pustaka (library research) dengan pendekatan deskriptif kualitatif, yang didasarkan pada analisis berbagai literatur dan dokumen resmi. Hasil kajian menunjukkan bahwa UKM Menwa UNEJ memberikan kontribusi yang signifikan dalam membangun karakter kebangsaan mahasiswa melalui kegiatan pelatihan, pengamanan acara kampus, dan pengabdian kepada masyarakat. Selain itu, Menwa juga aktif melakukan sosialisasi dan pelatihan deteksi hoaks sebagai upaya meningkatkan kesadaran literasi digital di kalangan mahasiswa.Namun, Artikel ini juga mencatat adanya beberapa kendala, seperti rendahnya partisipasi mahasiswa, keterbatasan literasi digital, dan minimnya sumber daya. Oleh karena itu, diperlukan dukungan institusional yang lebih kuat serta strategi kolaboratif agar program bela negara yang berbasis literasi digital dapat dilaksanakan dengan optimal dan berkelanjutan.